Low molecular weight and highly functional RCF lignin products as a full bisphenol a replacer in bio-based epoxy resins. Issue 46 (11th May 2021) - Van Aelst, Korneel; Van Sinay, Elien; Vangeel, Thijs; Zhang, Yingtuan; Renders, Tom; Van den Bosch, Sander; Van Aelst, Joost; Sels, Bert F.
Abstract : A lignocellulose-to-chemicals valorization chain is presented, wherein lignin oligomers obtained from reductive catalytic fractionation are used to synthesize BPA-free epoxy resins. Abstract : Herein, we present a full lignocellulose-to-chemicals valorization chain, wherein low molecular weight and highly functional lignin oligomers, obtained from reductive catalytic fractionation (RCF) of pine wood, were used to fully replace bisphenol A (BPA) for synthesizing bio-based epoxy resins.